The effect of institutional quality on economic performance: a cross country study - Şener, Pınar (My University, 2009)
Günümüzde, ülkeler arası gözlemlenen gelir farklılıkları araştırmacıları bu durumun nedenlerini incelemeye itmiştir. Neo klasik görüş, gelir farklılıklarını sermaye birikimi ve teknolojik değişime bağlarken, kurumsal yaklaşım, analizinin temelini kurumlara dayandırarak kurumsal altyapının önemini vurgular. Bu çalışmada, kurumsal iktisatın varsayımları temel alınarak, elli üç gelişmekte olan ülke için kurumsal kalitenin ekonomik büyüme üzerine olan etkisi 1998 ile 2007 yıllari arasında analiz edilmiştir. Tahmin metodu olarak statik panel veri analizi, kurumsal kalite göstergesi olarak da Dünya Bankası’nın Yönetişim göstergeleri tercih edilmiştir. Ampirik analiz sonuçları literatür ile tutarlı olup, analizde kullanılan altı kurumsal kalite göstergesinden üç tanesinin ekonomik büyümeye etkisi olduğu ortaya konmuştur. Bu göstergeler söz hakkı ve hesap verebilirlik, yolsuzluk kontrolü ve idari kalitedir. Demokrasi göstergesi olarak kullanılan söz hakkı ve hesap verebilirliğin ekonomik büyümeye negatif, yolsuzluk kontrolü ve idari kalitenin ise ekonomik büyümeye pozitif katkısı olduğu bulunmuştur. Ayrıca, hukukun üstünlüğü, hükümetin etkinliği ve siyasi istikrar ve şiddetsizlik göstergelerinin analizimizde incelenen ülkelerin ekonomik performansına katkısı olmadığı ortaya konmuştur. Kurumsal Kalite, Ekonomik Büyüme, Gelişmekte olan Ülkeler

Enormous income differences between rich and poor countries have recently intrigue researchers to investigate the causes of this situation. While neoclassical economists argue that capital accumulation and technological change lie behind these income differences, institutionalists, basing their analysis on institutions, emphasize the importance of institutional structure. In this study, by taking into consideration the assumptions of institutional economics, the effect of institutional quality on economic performance of fifty three developing countries is empirically tested over the period 1998-2007. To estimate the model, a static panel data analysis is used and as institutional quality proxies, world wide governance indicators of the World Bank are preferred. Being consistent with literature, the results of static panel data analysis show that only three institutional quality proxies have an impact on economic performance; these indicators are voice and accountability, regulatory quality and control of corruption. Voice and accountability, which is used as a proxy of democracy, has a negative effect but control of corruption and regulatory quality have a positive effect on economic performance of developing countries. Additionally, it is found that rule of law, government effectiveness and political stability and absence of violence do not have an impact on economic performance of the developing countries analyzed. Institutional Quality, Economic Growth, Developing Countries
Keywords: Ekonomi Politikası; Ekonomik Büyüme_Gelişmekte Olan Ülkeler; Kurumsal Kalite